2003
DOI: 10.1002/lsm.10219
|View full text |Cite
|
Sign up to set email alerts
|

Increase of enamel fluoride retention by low fluence argon laser in vivo

Abstract: We concluded that the use of argon laser at low energy density (10.74 J/cm(2)) significantly increases the fluoride retention in lased enamel which had approximately three times more fluoride than the unlased enamel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
5

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 28 publications
2
38
0
5
Order By: Relevance
“…Several literature studies also showed an enhanced fluoride adsorption [Tagomori and Morioka, 1989], uptake [Chin-Ying et al, 2004;Tepper et al, 2004;Schmidlin et al, 2007] and retention [Nammour et al, 2003;Demortier and Nammour, 2008] due to laser irradiation. Although several mechanisms were suggested to explain the increase in fluoride retention after laser irradiation, it seems that the surface roughness plays a role in increasing fluoride retention.…”
Section: Discussionmentioning
confidence: 99%
“…Several literature studies also showed an enhanced fluoride adsorption [Tagomori and Morioka, 1989], uptake [Chin-Ying et al, 2004;Tepper et al, 2004;Schmidlin et al, 2007] and retention [Nammour et al, 2003;Demortier and Nammour, 2008] due to laser irradiation. Although several mechanisms were suggested to explain the increase in fluoride retention after laser irradiation, it seems that the surface roughness plays a role in increasing fluoride retention.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is well absorbed in pigmented tissues, including hemoglobin and melanin, and in pigmented bacteria. Although not widely used in periodontal therapy, in operative dentistry the 488 nm argon laser is commonly used for curing composite resin (142) and bleaching teeth in the dental office, and the application for caries prevention has also been studied (127). The argon laser was approved by the FDA for oral soft tissue surgery and curing of composite materials in 1991 and for tooth whitening in 1995 (193).…”
Section: Characteristicsmentioning
confidence: 99%
“…These 80 air-samples were stored for 7 days in air with no turbulence [17]. In addition 80 samples EF-wat and 80 samples EFL-wat were stored for the same period in distilled water.…”
Section: Laser Enhanced Retention Of Fluoride In Enamelmentioning
confidence: 99%